2015
DOI: 10.1007/s10555-015-9576-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimal first-line chemotherapeutic treatment in patients with locally advanced or metastatic esophagogastric carcinoma: triplet versus doublet chemotherapy: a systematic literature review and meta-analysis

Abstract: There is a debate whether triplet or doublet chemotherapy should be used as a first-line treatment in patients with advanced or metastatic esophagogastric cancer. Therefore, here we will review the available literature to assess the efficacy and safety of triplet versus doublet chemotherapy as a first-line treatment in patients with advanced esophagogastric cancer. We searched MEDLINE, Embase, and CENTRAL (Cochrane Central Register of Controlled Trials) between 1980 and March 2015 for randomized controlled pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 42 publications
3
36
0
Order By: Relevance
“…This heterogeneity in treatment is undesirable, especially in case of unconventional treatment combinations, since second-line treatment options are often registered under the assumption that certain compounds have been administered in the first line. 25,26 Since the added value of the addition of an anthracycline to a platinum-fluoropyrimidine doublet remains uncertain, 15,[27][28][29] doublet chemotherapy tends to be the favored choice of firstline palliative treatment because of its better tolerance. Analysis of beyond first-line treatments is currently ongoing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This heterogeneity in treatment is undesirable, especially in case of unconventional treatment combinations, since second-line treatment options are often registered under the assumption that certain compounds have been administered in the first line. 25,26 Since the added value of the addition of an anthracycline to a platinum-fluoropyrimidine doublet remains uncertain, 15,[27][28][29] doublet chemotherapy tends to be the favored choice of firstline palliative treatment because of its better tolerance. Analysis of beyond first-line treatments is currently ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] However, the optimal first-line palliative systemic therapy regimen for metastatic esophagogastric cancer patients has not yet been identified. 6,14,15 Because of the lack of consensus on optimal palliative systemic treatment, making choices about the best approach for these patients is challenging, which can result in interhospital and interphysician variation in individual systemic treatment. [7][8][9][10][11] Triplet therapy, in which either an anthracycline or taxane is added to the platinum-fluoropyrimidine doublet, is suggested in international guidelines for patients in good condition, 8,10,12,13 but becomes increasingly controversial because of its toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In a large meta-analysis study that included twenty-one studies with a total of 3475 participants, triplet therapy was suggested to be superior to doublet therapy in patients with advanced gastric or esophageal cancer. However, the survival benefit is limited with increased risks for thrombocytopenia, infection, and mucositis (33). Having several factors contribute to development of UGCs and the existence of only few treatment options add extra challenge to our ability to treat them.…”
Section: Introductionmentioning
confidence: 99%
“…10.7/5.8 vs. 8.8/3.9 months) [23], or capecitabine and oxaliplatin, OS 8 months [24]. A recent meta-analysis showed a limited survival benefit of triplet chemotherapy with an increased risk of toxicity when compared to doublet chemotherapy [25]. Cisplatin and gemcitabine have a different side effect profile compared with oxaliplatin-based chemotherapy regimens.…”
Section: Discussionmentioning
confidence: 99%